Evaluation of Performance of Biochemistry Analytes Using Six Sigma Metrics in Clinical Laboratory of Nobel Medical College Teaching Hospital - Joshi, Bishal Raj; Rizal, Shikha; Jha, Sanjay Kumar; Bhattarai, Kushal; Majhi, Bhaktaraj; Chaudhary, Sanjeev Kumar; Shreewastav, Rupesh Kumar (Journal of Nobel Medical College, 2024)
Background: Six sigma metrics is a tool used in clinical laboratories that helps to quantitate the approximate number of analytical errors and provide an objective assessment of quality. This study aims to evaluate the performance of various biochemistry analytes using six-sigma metrics to identify areas for improvement and enhance overall quality control.Materials and Methods: This study is a cross sectional study conducted at the Clinical Chemistry Laboratory of Naya Lab, Nobel Medical College Teaching Hospital, Biratnagar that evaluated internal quality control and external quality control data of 18 routine biochemistry tests for a period of four months to calculate sigma value. The analysis was performed using a Beckmann Coulter automated biochemistry analyzer. Quality goal index values were calculated to find the reason behind lower sigma values